Analisis Penerimaan Retribusi Parkir Pada Pasar Alok Terhadap Pendapatan Asli Daerah Kabupaten Sikka Tahun (2018-2020) - Lusiana Lusiana; Henrikus Herdi; Pipiet Niken Auerlia (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to find out and analyze the Acceptance of Parking Retribution on Regional Original Revenue of Sikka Regency. The type of research used is descriptive-quantitative. Quantitative-descriptive is a method that aims to objectively create a picture or description of a situation using numbers starting from data collection, interpretation of the data as well as appearance and results. Data analysis techniques in this study use growth analysis formulas, effectiveness analysis formulas and contribution analysis formula. The results of this study indicate that the growth in parking fee receipts in Sikka district in 2018-2020 was not effective. The effectiveness of receiving parking fees in Sikka Regency from 2018-2020 is quite effective because parking officers are negligent in guarding the parking lot. The contribution of parking fee receipts to local revenue in Sikka district in 2018-2020 has fluctuated because revenue from parking fees is unequal each year and is unable to contribute to PAD.